(untitled) (Journal of Hama University, 2024)
The aim of the research was to identify the relationship between positive thinking and self-awareness among the sample of fourth-year students in the psychological counseling department, in addition to revealing the differences in positive thinking and self-awareness depending on a variable. the researcher relied on the descriptive analytical approach, as the research sample amounted to (51) students, and to achieve the research goals, the researcher used the scale of Dr. Fatima Khalifa Al-Sayed and Dr. Shorouk gharmallah Al-Zahrani (2023) and the scale of Hossam Mohammed Munshid (2013), and the research reached the following results: There is a direct correlation between positive thinking and self-awareness among the members of the research sample, the level of positive thinking and self-awareness was also high, and the results also showed that there were no significant differences between the average answers of the students of the research sample on the scales of positive thinking and self-awareness depending on the gender variable (male/female).